Comprehensive Stroke Centers and the ‘Weekend Effect’: The SPOTRIAS Experience - Albright, Karen C.; Savitz, Sean I.; Raman, Rema; Martin-Schild, Sheryl; Broderick, Joseph; Ernstrom, Karin; Ford, Andria; Khatri, Rakesh; Kleindorfer, Dawn; Liebeskind, David; Marshall, Randolph; Merino, José G.; et al. (Cerebrovascular diseases (Basel, Switzerland), 2012)
Background and Purpose: Previous studies have found mortality among ischemic stroke patients to be higher on weekends. We sought to evaluate whether weekend admission was associated with worse outcomes in a large comprehensive stroke center (CSC) cohort. Methods: Consecutive ischemic stroke patients presenting within 6 h of symptom onset were identified using the 8 CSC SPOTRIAS (Specialized Programs of Translational Research in Acute Stroke) database. Patients who received intra-arterial therapy or who were enrolled in a nonobservational clinical trial were excluded. All patients meeting the inclusion criteria were then divided into two groups: weekday admissions or weekend admissions. Weekend admission was defined as Friday 17:01 to Monday 08:59. The remainder were classified as weekday admissions. Multivariate logistic regression was used, adjusting for age, stroke severity on admission [according to the National Institutes of Health Stroke Scale (NIHSS)] and admission glucose, in order to compare the outcomes of the weekend versus the weekday groups. Results: Eight thousand five hundred and eighty-one subjects from the combined SPOTRIAS database were screened from 2002 to 2009; 2,090 (24.4%) of these met the inclusion criteria. There was no significant difference in tissue plasminogen activator treatment rates between the weekday and weekend groups (58.5 vs. 60.4%, p = 0.397). Weekend admission was not a significant independent predictor of inhospital mortality (8.4 vs. 9.9%, p = 0.056), length of stay (4 vs. 5 days, p = 0.442), favorable discharge disposition (38.0 vs. 42.2%, p = 0.122), favorable functional outcome at discharge (41.6 vs. 43.4%, p = 0.805), favorable 90-day functional outcome (54.2 vs. 46.9%, p = 0.301), or 90-day mortality (18.2 vs. 19.8%, p = 0.680) when adjusting for age, NIHSS and admission glucose. Conclusions: In this large cohort of ischemic stroke patients treated at CSCs, we did not observe the ‘weekend effect.’ This may be due to access to stroke specialists 24 h a day on 365 days a year, nurses with stroke experience and the organized system for delivering care that is available at CSCs. These results suggest that EMS protocol should be reexamined regarding the preferential delivery of weekend stroke victims to hospitals that provide all levels of reperfusion therapy. This further highlights the importance of organized stroke care.